The Effect of Service Quality and Marketing Programs on Third Party Funds - Putri Rahmawati Septya; Pramudya A Taufik; Zacky Yusuf (Yayasan Ilomata, 2019)
Competition between banks is currently very tight. To win the competition the bank must pay attention to the needs and desires of its customers. The quality of services and marketing programs is thought to play an important role in the growth of Third Party Funds. This study aims to examine the Effect of Service Quality and Marketing Programs on Third Party Funds at DKI Bank Sunter Branch. This research uses quantitative research methods by distributing questionnaires. The population of this research is all new customers in 2018 at DKI Bank Branch Sunter, which numbered 1000 customers, with a sample of 150 respondents. The results showed that partially and simultaneously the quality of services and marketing programs had a significant effect on Third Party Funds